Minocycline inhibits microglial activation and alleviates depressive-like behaviors in male adolescent mice subjected to maternal separation. (September 2019) - Han, Yue; Zhang, Lijuan; Wang, Qiaozhi; Zhang, Dingding; Zhao, Qiuying; Zhang, Jinqiang; Xie, Lei; Liu, Guangyi; You, Zili
Highlights: MS primers microglial activation characterized by pro-inflammatory phenotype in offspring mice. "Two-hit" of MS combined with restraint stress induces neurogenesis impairments and depressive-like behaviors in male mice. Promoting microglia pro-neurogenesis phenotype with minocycline can reverse early adversity-induced behavioral deficits. Abstract: Exposure to early adversity increases vulnerability to psychiatric disorders in later life. Microglia-mediated inflammation has been linked to psychopathology, so such inflammation may be a target for treating depression. Using a model of depression involving adolescent male C57BL/6J mice subjected to maternal separation, we explored whether using minocycline to mitigate inflammation can alleviate depression-like behaviors. Between postnatal days 1 and 14, male mice were separated from their mothers for 3 h per day. Minocycline (20 mg/kg) was administered intraperitoneally once daily for 2 weeks starting one week after weaning. Then the male mice were subjected to a second stress for 2 weeks. Results from the sucrose preference test, forced swimming test, and open field test showed that maternal separation did not obviously alter behavior of the male mice, but it did increase the risk of depression-like behaviors following a second stress. This increased risk disappeared if minocycline was given preemptively before the second stress. Maternal separation and second stress up-regulated pro-inflammatory markers and down-regulated anti-inflammatory markers in the hippocampus, and they activated microglia and promoted pro-inflammatory transitions in microglia. All these effects were reversed by minocycline. These changes in inflammatory processes correlated with changes in neurogenesis and BDNF expression in the hippocampus. Our results in this mouse model suggest the potential of minocycline for treating psychiatric disorders induced by early adversity.